Perioperative management of the patient with cardiovascular disease undergoing non-cardiac surgery. Issue 8 (August 2016) - Vats, Anurag; Marbaniang, Monalisa J.; Howell, Simon J.
Abstract: Cardiac complications are the most common cause of postoperative morbidity and mortality. Thorough preoperative risk assessment and stratification allow clear identification of higher risk patients who would benefit from preoperative optimization and risk reduction strategies. Newer investigations improve the predictive value of contemporary risk indices. Atrial fibrillation and heart failure pose more risk than previously thought, even for minor non-cardiac surgery.